Study of daylighting and building performance of atria buildings in Malaysia / Sabarinah Sh Ahmad, Azni Zain-Ahmed and Julitta Yunus - Sh Ahmad, Sabarinah; Zain-Ahmed, Azni; Yunus, Julitta (Research Management Institute (RMI), 2011)
The development of atrium buildings in Malaysia is growing in number. This design trend are recognised as one of the most popular and environmentally stimulating spaces of today's architecture, at once shutting out the often harsh natural environment and yet benefiting from its natural light. Incorporated into many forms of buildings, an atrium can be used to stimulate the outdoors and to admit natural light and solar heat into the indoor space. The passive solar features incorporated in atrium is utilising the usage of daylight contribution that can save energy. The daylighting aspects of the atrium need a careful design to accomplish visually attractive as well as energy-efficient building criteria. However, instead of creating the potential for both increased energy savings and an improved indoor environment, if the atrium is only artificially lit or heated it may waste more energy than it saves. An atrium's characteristic is the roof: a careful design of the roof fenestration systems limits glare, mitigates passive solar heating effects and supplies adequate daylighting and minimizes sunlight. Therefore, atrium roof form and structure are important architectural design elements, where it can influence daylight availability within the space and, therefore, lighting energy consumption. A common feature of most studies were that the atrium roof was left as an open, unobstructed void, which is obviously very different from the conditions existing in real atria [8]. Therefore, this is an area not studied before. Their studies were strongly recommending further analysis on several variations of roof structures and roof glazing and their impact on the distribution of daylight.